Enhanced in situ H2O2 electrosynthesis and leachate concentrate degradation through side-aeration and modified cathode in an electro-Fenton system - Zhang, Fanbin (Waste management (New York, N.Y.), 2024)
Copyright © 2024 Elsevier Ltd. All rights reserved.